Dynamics of a recovering Arctic bird population: the importance of climate, density dependence, and site quality. Issue 7 (1st October 2015) - Bruggeman, Jason E.; Swem, Ted; Andersen, David E.; Kennedy, Patricia L.; Nigro, Debora
Abstract : Intrinsic and extrinsic factors affect vital rates and population‐level processes, and understanding these factors is paramount to devising successful management plans for wildlife species. For example, birds time migration in response, in part, to local and broadscale climate fluctuations to initiate breeding upon arrival to nesting territories, and prolonged inclement weather early in the breeding season can inhibit egg‐laying and reduce productivity. Also, density‐dependent regulation occurs in raptor populations, as territory size is related to resource availability. Arctic Peregrine Falcons ( Falco peregrinus tundrius ; hereafter Arctic peregrine) have a limited and northern breeding distribution, including the Colville River Special Area (CRSA) in the National Petroleum Reserve–Alaska, USA. We quantified influences of climate, topography, nest productivity, prey habitat, density dependence, and interspecific competition affecting Arctic peregrines in the CRSA by applying the Dail‐Madsen model to estimate abundance and vital rates of adults on nesting cliffs from 1981 through 2002. Arctic peregrine abundance increased throughout the 1980s, which spanned the population's recovery from DDT‐induced reproductive failure, until exhibiting a stationary trend in the 1990s. Apparent survival rate (i.e., emigration; death) was negatively correlated with the number of adult Arctic peregrines on the cliff the previous year, suggesting effects of density‐dependent population regulation. Apparent survival and arrival rates (i.e., immigration; recruitment) were higher during years with earlier snowmelt and milder winters, and apparent survival was positively correlated with nesting season maximum daily temperature. Arrival rate was positively correlated with average Arctic peregrine productivity along a cliff segment from the previous year and initial abundance was positively correlated with cliff height. Higher cliffs with documented higher productivity (presumably indicative of higher‐quality habitat), are a priority for continued protection from potential nearby development and disturbance to minimize population‐level impacts. Climate change may affect Arctic peregrines in multiple ways, including through access to more snow‐free nest sites and a lengthened breeding season that may increase likelihood of nest success. Our work provides insight into factors affecting a population during and after recovery, and demonstrates how the Dail‐Madsen model can be used for any unmarked population with multiple years of abundance data collected through repeated surveys.